Enhancement of Hydrothermally Co3O4 Thin Films as H2S Gas Sensor by Loading Yttrium Element (Baghdad Science Journal, 2019)
The gas sensing properties of Co3O4 and Co3O4:Y nano structures were investigated. The films were synthesized using the hydrothermal method on a seeded layer. The XRD, SEM analysis and gas sensing properties were investigated for Co3O4 and Co3O4:Y thin films. XRD analysis shows that all films are polycrystalline in nature, having a cubic structure, and the crystallite size is (11.7)nm for cobalt oxide and (9.3)nm for the Co3O4:10%Y. The SEM analysis of thin films obviously indicates that Co3O4 possesses a nanosphere-like structure and a flower-like structure for Co3O4:Y.The sensitivity, response time and recovery time to a H2S reducing gas were tested at different operating temperatures. The resistance changes with exposure to the test gas. The results reveal that the Co3O4:10%Y possesses the highest sensitivity around 80% at a 100oC operating temperature when exposed to the reducing gas H2S with 0.8sec for both recovery and response times.